Application of historic datasets to understanding open solar flux and the 20th-century grand solar maximum. 1. Geomagnetic, ionospheric, and sunspot observations - Lockwood, Mike; Owens, Mathew J.; Barnard, Luke A.; Scott, Chris J.; Frost, Anna M.; Yu, Bingkun; Chi, Yutian (Frontiers in Astronomy and Space Sciences, 2022)
We updated annual mean reconstructions of near-Earth interplanetary conditions and (signed) open solar flux FS for the past 186 years. Furthermore, we added observations for solar cycle 24 to refine regressions and improved allowance for orthogardenhose and folded (a.k.a., switchback) heliospheric flux from studies using strahl electrons. We also improved the allowance made for the annual mean gardenhose angle of the interplanetary magnetic field. We used both multiple regression with interplanetary magnetic field B and solar wind speed VSW and linear regression with the function BVSWn and demonstrated that the latter gives correlations that are not significantly lower than those given by the former. We conducted a number of tests of the geomagnetic indices used, of which by far the most important is that all four usable pairings of indices produce almost identical results for B, VSW, and FS. All reconstructions were given full 2σ uncertainties using a Monte Carlo technique that generates an ensemble of 1 million members for each pairing of indices. The long-term variations of near-Earth interplanetary field B and open solar flux FS were found to closely match those of the international sunspot numbers but VSW show a significantly different variation. This result explains why of the two peaks of 20th-century grand solar maximum, the range geomagnetic indices give a larger second peak, whereas the diurnal variation indices give a first peak that is larger, as it is for sunspots. We found that the increase in solar cycle averages of FS was between 2.46 × 1014 Wb in 1906 and 4.10 × 1014 Wb in 1949, the peak of the grand maximum, and hence, the rise in open flux was by a factor of 67%.